NEGOTIATING JOYFUL ENGLISH TEACHING WITHIN BUREAUCRATIC CONSTRAINTS: A PHENOMENOLOGICAL STUDY OF INDONESIAN ENGLISH TEACHERS - Rahmad Alimin Lauli; Abdurrohman Septiadi (FKIP Universitas Alwashliyah Medan, 2026)
This study aims to explore English teachers’ experiences in implementing joyful learning amid administrative and bureaucratic constraints within schools. Employing a qualitative phenomenological design, the research investigates the meanings, challenges, and strategies developed by teachers in their daily instructional practices. The participants were 12 English teachers from various educational levels in North Sumatra, selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and analysis of instructional as well as administrative documents. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña involving data reduction, data display, and conclusion drawing. The findings reveal that teachers perceive joyful learning as an approach that enhances student engagement, motivation, and positive classroom atmosphere; however, its implementation is frequently constrained by administrative burdens such as curriculum documentation, performance reports, and formal evaluation demands. Teachers experience tension between pedagogical ideals and bureaucratic expectations, yet they develop adaptive strategies including integrated planning, professional collaboration, and the use of simple technologies to sustain instructional quality. The study concludes that the successful implementation of joyful learning is strongly influenced by institutional support and educational policies that prioritize teachers’ pedagogical needs. Therefore, it is recommended that policymakers reconsider teachers’ administrative workload and strengthen professional development programs that promote a balanced integration of systemic demands and humanistic teaching practices.